Herpes simplex virus type 1 infection: a sexually transmitted infection of adolescence?. Issue 5 (1st October 2002) - Cowan, F M; Copas, A; Johnson, A M; Ashley, R; Corey, L; Mindel, A
Abstract : Objectives: To examine the factors associated with antibodies to herpes simplex virus type 1 (HSV-1). Design: Cross sectional study with HSV-1 antibody testing performed by University of Washington western blot assay. Setting: Central London STD clinic (1990–1) and central London blood donation centre (1992). Participants: Representative sample of 869 new and rebooked GUM clinic attenders and 1494 consecutive blood donors. Results: The prevalence of HSV-1 antibody among clinic attenders was 60.4% (95% CI 57.0 to 63.7) and among donors was 46.1% (95% CI 43.5 to 48.7). HSV-1 antibody was independently associated with increasing age in both populations (p<0.001). Among clinic attenders, HSV-1 was less common among heterosexual men than women and homosexual men (p<0.005), and was more common among black people (p=0.001) and those of lower socioeconomic status (p=0.05). Among blood donors, being single rather than married was independently associated with HSV-1 infection (p=0.03). Early age at first intercourse was strongly associated with presence of HSV-1 in both populations. The adjusted odds of HSV-1 among GUM clinic attenders was 0.37 (95% CI 0.21 to 0.65) for someone aged 20 at first intercourse compared with someone aged ≤15. Among blood donors, those aged 20 had an adjusted odds of 0.64 (95% CI 0.39 to 1.05) compared with someone aged 15. HSV-1 was not associated with increasing number of lifetime partners after adjustment for other factors. Conclusions: Genital herpes due to HSV-1 antibody is increasing in the United Kingdom, particularly among young people. In this study we found that HSV-1 was strongly associated with early age of first sexual intercourse, which may reflect the sexual practices of people initiating sex in this age group.